Tumor Detection from Mammograms using Thresholding and Morphological operations - K.Sudha Rani, Dr.; Sri Laxmi, D.; V.Shobana, D.; Mani Kumari, K. (International Journal of Engineering and Technology, 2018)
According to the Statistics released by World health organization (WHO), Breast Cancer rate is growing day by day. And this disease is significant cause for death amongst women. Several image processing techniques have been developed for identification, detection and segmentation of breast cancer. Breast cancer is uncertain in nature, so prevention becomes impossible. Thus, early detection of a tumor in the breast is the only way to cure breast cancer. In this research, breast tumor detection in a Mammogram is done by Histogram, Thresholding, and Advanced Morphological Techniques and is being compared with general practitioners and specialist result.Â Â Â